RE- BRANDING: Study on the repositioning of Banco Intermedium (Banco Inter) - Souza, Juliana Lopes de Almeida; Patrocínio, Rachel Farias do; Costa, Mariana de Oliveira; Sá, Samara de Oliveira (Archives of Business Research, 2019)
This study addresses the brand repositioning of Banco Intermedium. The objective of the study was to understand what the brand positioning was like for some years and how it has been working its repositioning since 2017. We also seek to investigate how the repositioning contributed to the improvement of the institution's image and performance in the marketplace. As a methodology, secondary data searches were adopted through the Internet, through the brand's websites and online social networks, and as a method for obtaining primary data, interviews were conducted with clients, and with a branding specialist and employee of Banco Inter, in order to understand the internal and external perception of the brand.